Audit of deaths less than a week after admission through an emergency department: how accurate was the ED diagnosis and were any deaths preventable?. Issue 10 (27th September 2007) - Nafsi, Tabassum; Russell, Rob; Reid, Cilla M; Rizvi, Syed M M
Abstract : Aim: To review the causes of death in patients admitted via the emergency department (ED) who died within 7 days of admission and to identify any ways in which ED care could have been better. The study also aims to compare the diagnosis made in the ED and the mortality diagnosis. Methods: A retrospective study; subjects were all patients who attended the ED over 4 months and died within 7 days of admission. The paramedics' notes, ED case cards, inpatient medical notes and details of postmortem findings were examined to identify the time and date of arrival in the ED, presenting complaint, provisional diagnosis made by the ED, treatment plan devised by the ED, diagnosis made in wards, and the cause of death as issued on death certificates or from postmortem findings. Summary sheets of cases where the care provided by the emergency department could have been improved were reviewed, errors were identified and deaths were classified as preventable or unpreventable. Results: Database revealed 3521 admissions via the ED over 4 months, of which 95 cases (2.69%) died within 7 days of admission. 78 patients (82.1% of cases) were appropriately diagnosed and managed whereas 17 (17.87% of cases) were identified with deficiencies in either the diagnosis or the management provided in the ED. We reviewed the quality of care provided in the ED for these cases and rated deaths according to our preventability criteria: 5 (5.26%) deaths were unpreventable despite the deficiency in care provided in the ED; 3 (3.15%) deaths were definitely preventable; 3 (3.15%) were probably preventable; and 6 (6.31%) were possibly preventable deaths. Conclusion: The ED is playing a good role in the management of critically ill patients, with appropriate diagnosis and management in 82% of cases. Training of junior doctors is required to prevent occurrence of errors and thus preventable deaths, but all deaths are not preventable. New guidelines for sepsis management and management of undifferentiated clinical presentations are being introduced and we intend to audit the implications of new guidelines.